Impact of in-kind benefits on tax efficiency: A case study of PT Kurnia Luwuk Sejati - Tandiawan, Vira; Rahman Mus, Abdul; Muhammad Su’un; Asri Ady Bakri (Kasetsart Journal of Social Sciences, 2026)
Tax efficiency is one of the determinants of performance and sustainability of companies all over the world. This research analyzes the level of Indonesian tax efficiency at PT Kurnia Luwuk Sejati in Luwuk Indonesia in the presence of in-kind benefits. The objective of the research is to investigate as to how these benefits like housing, transportation etc. can be used as a strategy to lessen the tax outflows. The data were analyzed in a quantitative research design and data collection was conducted applying financial records and employee benefit reports in selecting a sample of employees. The results highlight that such an awareness of the provisions of the law, particularly Minister of Finance Regulation No 66/2023, enables a company to adopt an appropriate tax strategy. In conclusion, in kind benefits help improve tax efficiency provided that these benefits are taken into account in planning the company’s tax structures. This research adds to the existing literature of in-kind local contribution by giving some particulars into the use of such benefits in Indonesia that would be interesting for other companies wishing to increase their operational tax efficiency. The findings of this study recommend organizations to align their tax and regulatory strategies in an optimal manner which abides by regulation changes while maximizing tax efficiency of the company. Overall, this research emphasizes the importance of tax planning strategy in improving financial performance and competitiveness of the firm within a more complex regulatory framework.